2015
DOI: 10.3390/rs70709390
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the Land Surface Phenology of Europe Using Decadal MERIS Data

Abstract: Land surface phenology (LSP), the study of the timing of recurring cycles of changes in the land surface using time-series of satellite sensor-derived vegetation indices, is a valuable tool for monitoring vegetation at global and continental scales. Characterisation of LSP and its spatial variation is required to reveal and predict ongoing changes in Earth system dynamics. This study presents and analyses the LSP of the pan-European continent for the last decade, considering three phenological metrics: onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 53 publications
4
19
0
2
Order By: Relevance
“…In these areas, vegetation dynamics show highly stable intra-and inter-annual patterns specially in the "very cold" and "cold" climates ( Figure 3b-c), resulting probably from the low inter-annual variability of temperature and illumination as main climatic constraints for vegetation growth in these regions [77,78]. Other studies based on phenometric approach have shown similar results with low variability in greenness onset and/or end of senescence [79] and length of growing season [80].…”
Section: Discussionsupporting
confidence: 63%
“…In these areas, vegetation dynamics show highly stable intra-and inter-annual patterns specially in the "very cold" and "cold" climates ( Figure 3b-c), resulting probably from the low inter-annual variability of temperature and illumination as main climatic constraints for vegetation growth in these regions [77,78]. Other studies based on phenometric approach have shown similar results with low variability in greenness onset and/or end of senescence [79] and length of growing season [80].…”
Section: Discussionsupporting
confidence: 63%
“…Field observations have been widely and successfully conducted, providing detailed information at the species level based on individual plant observations across many countries [8], and observation networks have been established to support these ongoing observations [9,10]. A large number of studies have been conducted to observe vegetation phenology at short-and/or long-term scales across many regions [11], but these observations have focused mainly on developmental switches within individual species [12] and cannot reveal integrative phenology patterns on the biome or broader scale, and this research is often time inefficient and labor intensive [1,13]. Alternatively, satellite-based methods, which rely on vegetation indexes (e.g., NDVI) provide a powerful, integrative, and objective tool for monitoring and characterizing key phenological metrics (such as the start of the season (SOS), end of the season (EOS), and length of the season (LOS)) at regional and global scales across long time-series, serving as an excellent complement to the shortage of field observations [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MTCI has been used to discriminate between C3 and C4 grasses (Foody and Dash, 2007) and to monitor vegetation phenology at the sub-regional (Boyd et al, 2011) and continental scales (Rodriguez-Galiano et al, 2015;Crabbe et al, 2016). Regarding canopy N detection, most applications were aimed at agricultural crops using MTCI values computed from in situ hyperspectral reflectance data (Tian et al, 2011;Clevers and Gitelson, 2013;Li et al, 2014).…”
mentioning
confidence: 99%